A multiscale model for quantifying fiber orientation effects on the tensile properties of 3D printed Engineered Cementitious Composites (3DP-ECC). (1st June 2023) - Pang, Zhiming; Lu, Cong; Li, Baoshan; Wang, Jiajie
Abstract: The lack of steel reinforcement in conventional 3D concrete printed structures leads to susceptibility to damage during construction. 3D printed Engineered Cementitious Composites (3DP-ECC) are attracting attention as alternatives for providing additional reinforcement by incorporating fibers in 3D concrete printing. However, the effect of the fiber orientation distribution on the tensile performance of 3DP-ECC has not been quantitatively evaluated. This study established an approach for quantifying the fiber orientation distribution for printing nozzles with different shapes and sizes using probability density functions. The effect of the fiber orientation on the tensile behavior of 3DP-ECC was further quantitatively evaluated by analyzing the fiber number, load transfer distance, and fiber bridging properties. A multiscale model was used to evaluate the tensile behavior of 3DP-ECC. The proposed model was validated by analyzing specimens fabricated using casting, 3DP-20 mm, and 3DP-8 mm nozzles, showing good agreement with the experimental results. Highlights: An approach for quantifying the fiber orientation distribution. A multiscale model to simulate the tensile behavior of 3DP-ECC. Load transfer efficiency for 3DP-ECC fabricated with different nozzles.